Automatic Milkfish Feeding System Based on Fuzzy Logic on Microcontroller - Fadhiel Fadhiel Naufal Huda; Silvester Ariski Tobi; Fadhiel Naufal Huda; Khoirul Kodri Nasution; Muhamad Ariq Maulana; Hanatasya Ramadhan; Ahmad Fahrezzi; Nailah Azzahra Cinthari; Willa Wulandari; Bunga Ligar Balebat; Muhammad Rayhan Kurniawan; Stilo Farrel Ticoalu; Muhammad Faiz Assariy (Batrisya Education, 2025)
Dear Editorial Team, I hope this message finds you well. Please find attached our manuscript entitled